2024
DOI: 10.3390/jcm13092709
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Lesions in Panoramic Radiography and CBCT Imaging—Assessment of AI’s Diagnostic Accuracy

Wojciech Kazimierczak,
Róża Wajer,
Adrian Wajer
et al.

Abstract: Background/Objectives: Periapical lesions (PLs) are frequently detected in dental radiology. Accurate diagnosis of these lesions is essential for proper treatment planning. Imaging techniques such as orthopantomogram (OPG) and cone-beam CT (CBCT) imaging are used to identify PLs. The aim of this study was to assess the diagnostic accuracy of artificial intelligence (AI) software Diagnocat for PL detection in OPG and CBCT images. Methods: The study included 49 patients, totaling 1223 teeth. Both OPG and CBCT im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(92 reference statements)
1
0
0
Order By: Relevance
“…Similarly, Orhan et al (2020) reported that AI systems could effectively identify PLs in cone-beam computed tomography (CBCT) scans, highlighting the potential for AI to support clinical decision-making in endodontics [ 18 ]. Similar results were shown in our 2024 study on the diagnostic accuracy of Diagnocat for PL detection in the PAN and CBCT images of one patient cohort [ 19 ]. The sensitivity of the AI for PL detection via PAN was 33.33%, with significantly higher metrics for CBCT (77.78%).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Orhan et al (2020) reported that AI systems could effectively identify PLs in cone-beam computed tomography (CBCT) scans, highlighting the potential for AI to support clinical decision-making in endodontics [ 18 ]. Similar results were shown in our 2024 study on the diagnostic accuracy of Diagnocat for PL detection in the PAN and CBCT images of one patient cohort [ 19 ]. The sensitivity of the AI for PL detection via PAN was 33.33%, with significantly higher metrics for CBCT (77.78%).…”
Section: Discussionsupporting
confidence: 87%